2005
DOI: 10.1055/s-2005-917087
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Chemistry of Quinoneimides

Abstract: This account describes the developments in quinoneimide chemistry during the last two decades, emphasizing the addition of weak nucleophilic systems leading to cycloadducts in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In situ oxidation of N-tosylaniline in the presence of H 2 O gives an intermediate A, which undergoes aromatization to form N-tosyl-p-aminophenol. This is followed by further oxidation to afford an electrophilic intermediate pquinone monosulfonimide C. [8] With the catalysis of the CF 3 COOH generated in the oxidation reactions, 5-aminocoumaran is constructed from the Michael addition of intermediate C with 4-methoxystyrene and a subsequent intramolecular cyclization. [9] Trace amounts of N-tosyl-p-aminophenol were detected during the oxidation reaction.…”
Section: Entry 19)mentioning
confidence: 99%
“…In situ oxidation of N-tosylaniline in the presence of H 2 O gives an intermediate A, which undergoes aromatization to form N-tosyl-p-aminophenol. This is followed by further oxidation to afford an electrophilic intermediate pquinone monosulfonimide C. [8] With the catalysis of the CF 3 COOH generated in the oxidation reactions, 5-aminocoumaran is constructed from the Michael addition of intermediate C with 4-methoxystyrene and a subsequent intramolecular cyclization. [9] Trace amounts of N-tosyl-p-aminophenol were detected during the oxidation reaction.…”
Section: Entry 19)mentioning
confidence: 99%
“…Related investigations also revealed that Lewis acid mediated reactions of o-quinoneimines and o-quinonediimines followed significantly different pathways depending upon the nature of the Lewis acid, allylsilane and temperature. 4 A report on a similar annulation reaction of silyl enol ethers and an o-quinone leading to the formation of benzofuran derivatives is also worth mentioning here. 55 The photochemical annulation reaction of 1,2-naphthoquinone 110 with allyltrimethylsilane 111 also furnished a dihydrobenzofuran derivative 112 (Scheme 35).…”
Section: O-quinones In Phosphine-mediated Reactionsmentioning
confidence: 94%
“…Quinazolinones are one of the most prevalent heterocycles that are diversely found in many natural products, drugs, and biologically important molecules. As shown in Figure , several of these compounds are also known to be cytotoxic, antifungal, hypnotic, antiendotoxic, etc. to inhibit insulin secretion and smooth muscle contractile activity by attacking the KATP channel activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported syntheses of these derivatives rely on precursors, such as ortho -amino or ortho -nitro benzoic acids. Owing to the importance of quinazolinones, various synthetic efforts have been made to prepare them from a variety of starting materials. …”
Section: Introductionmentioning
confidence: 99%